(3QSGdI aj GdYQhVs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3CYde Cf GdOSJhQ Gdeaff ai EfTGA cd af Shi GdEdgi gh JbSje GdehVhY Gdcdi s
(3BNQgG (B:s
(3hgh jgOi GdSHjd hdG jfaY bGd hdG bjd Je JMQjQ JMbjbg GdebGe dedG Ndjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG Jedc jQLY Edi SfI (B1239 (3g` HGSe edG YHO Gddg GdYHOdi hba Ydi ChdGOIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI GdMLjGJ GdehUd (B(115) s
Keywords: (3GdeLGejYs